Identifikasi Benturan Kebiasaan Masyarakat Badui Dengan Hukum Positif Indonesia - Monica Amanda; Fadjrin Wira Perdana; Irwan Irwan; Doharman Lumban Tungkup; Miran Miran (Jurnal Indonesia Sosial Sains, 2022)
The Badui tribe is one of the indigenous tribes in Indonesia that still survives to this day. Geographically, the Badui tribe is close to the national capital. However, this does not necessarily make the Badui tribe eliminate the customs and laws that apply to the tribe, so it often clashes with positive law in Indonesia. This study aims to identify the clash of Badui habits with positive Indonesian law. The qualitative approach method was used to collect data and analysis. Data were collected by observation and literature study. The results show that the clash between the habits that develop in the Badui community and the provisions of positive law is a factual condition that occurs in society. For this reason, it is essential to carry out legal acculturation so that the Badui Customary Law can run in harmony with positive Indonesian law.